2020
DOI: 10.3390/ma13173834
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GelMA Hydrogel Coatings on Corrosion Resistance and Biocompatibility of MAO-Coated Mg Alloys

Abstract: Micro-arc oxidation (MAO) treatment is a simple and effective technique to improve the corrosion resistance for magnesium alloys. However, the presence of micro-pores and cracks on the coatings provides paths for corrosive ions to penetrate into and react with the substrate, limiting the long-term corrosion resistance. In this paper, we designed a composite coating with which GelMA hydrogel coatings with varying thicknesses were prepared on the surface of MAO-coated magnesium alloys via a dip-coating method, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…The Fourier transform infrared spectroscopy results showed that the GelMA-T scaffolds had two typical absorption peaks. The absorption peak at 3,289 cm −1 corresponded to the stretching vibration of the N-H peptide bond, whereas the absorption peak at 1,663 cm −1 was the stretching vibration of the C=O double bond (Figure 1B), which is consistent with previously reported results for GelMA (Weng et al, 2020;Da Silva et al, 2021).…”
Section: Materials Characterizationsupporting
confidence: 92%
“…The Fourier transform infrared spectroscopy results showed that the GelMA-T scaffolds had two typical absorption peaks. The absorption peak at 3,289 cm −1 corresponded to the stretching vibration of the N-H peptide bond, whereas the absorption peak at 1,663 cm −1 was the stretching vibration of the C=O double bond (Figure 1B), which is consistent with previously reported results for GelMA (Weng et al, 2020;Da Silva et al, 2021).…”
Section: Materials Characterizationsupporting
confidence: 92%
“…2 . It exhibited absorbance from 3411 to 3289 cm −1 confirming the presence of peptide bonds (mainly N–H stretching) [ 38 ]. The obvious absorbance peak at 1645 cm −1 could be assigned to C O stretching vibration, and the peak at 1531 cm −1 was assigned to C–N stretching plus N–H bending.…”
Section: Resultsmentioning
confidence: 99%
“…When a capacitor is omitted from the circuit, no current can flow because, when the capacitor is charged, the current will not pass, and the circuit will be cut off. The dense oxide layer on the surface of the titanium also has this effect and, such as a capacitor after being fully charge, disrupts the electrical circuit by reducing the corrosion rate [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. Based on the EIS diagrams and the obtained data, it can be concluded that the corrosion resistance of the sample with plasma electrolytic oxidation coating is better than that of the uncoated sample.…”
Section: Resultsmentioning
confidence: 99%